El Derecho de Vivir en Paz: quem matou Victor Jara? (Tempo e Argumento, 2022)
The review in question brings the look and perspectives of a historian of Latin American songs on the documentary "Massacre no Estádio", by North American director Bent-Jorgen Perlmutt, premiered on Netflix streaming in 2019, about the last days of Chilean singer and songwriter Victor Jara.
Keywords: review; documentary review; Victor Jara